ANALISIS DIMENSI KUALITAS PELAYANAN DAN PENGARUHNYA TERHADAP LOYALITAS WAJIB PAJAK RESTORAN DENGAN KEPUASAN SEBAGAI VARIABEL MEDIATOR - Sefnedi Indra (Jurnal Universitas Paramadina, 2013)
AbstractTaxing revenue plays important role in budgeting of every country andregion. One of regions that depends on its revenue from restaurant taxingsector is regency of West Pasaman. Therefore, regional taxing managementbecames more crutial and affected by the customer loyalty. Among the broadfactors that are able to impact restourant taxing customer namely servicequality and customer satisfaction. The purpose of this research is toinversigate the mediating role of customer satisfaction on the relationshipbetween service quality dimensions and customer loyalty. This researchconceptualizes the service quality consists of five dimensions namelytangibles, empathy, reliability, responsiveness and assurance. The researchpopulation is all restaurant taxing customers located in regency of WestPasaman which accounted for 98 people and considered as researchrespondent. In order to test hypotheses development, this research performsmultiple and hierarchical regressions by performing Statistical Package forSocial Science (SPSS) version 19.0. The result of analysis shows that 1)Dimensions of empathy, reliability, responsiveness and assurancesignificantly influence restaurant taxing customer loyalty, while dimensionof tangible did not have significant effect. 2) Dimensions of tangibles,empathy, reliability, responsiveness and assurance significantly influencerestaurant taxing customer satisfaction. 3) Customer satisfactionsignificantly influences restaurant taxing customer loyalty. 4) Customersatisfaction plays as mediating variable on the relationship betweendimensions of empathy, reliability, responsiveness, assurance and restauranttaxing customer loyalty. 5) The results of analysis provide practicalcontribution and recommendation to enhancing customer satisfaction byimplementing better service quality.